Perceived teacher self-efficacy relating to student diversity in mainstream classrooms - Kärki, Eline (2022)
The global inclusive education movement advocates that, children with special needs should be accommodated for in mainstream schools. Many classroom teachers however do not feel adequately equipped to cater to these diverse needs. This study investigated the influence of inclusive education on the self-efficacy of mainstream classroom teachers. It also tested whether the number of years of teaching experience has influence on how well a teacher collaborates with others, manages behavior, and engages students. The data for this quantitative research was gathered in 2013 using questionnaires which were sent to classroom teachers, in 68 schools in Eastern Finland. Two scales were combined to measure teacher self-efficacy in collaboration, behavior management and student engagement. Student diversity is defined as pupils falling into the three tiers of the support system, as well as those with attention deficiency and behavior issues. To find the relation between the variance of student diversity and the self-efficacy variables, Spearman’s and Pearson’s correlations were used. In exploring the relation of teaching experience with the self-efficacy variables ANOVA was applied. Results show that there is a significant negative correlation between the number of students with attention deficiency/behavior problems and teachers’ perceived self-efficacy in behavior management. The number of students with intensified or special support however, does not appear to be associated with any of the self-efficacy variables or amount of teaching experience. It could be suggested as a practical implication that teachers’ behavior management skills can be improved with specific training.